2013
DOI: 10.1080/14786419.2013.800977
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water-soluble vitamins in multivitamin dietary supplements and in artichokes by micellar electrokinetic chromatography

Abstract: Several procedures of extraction with solvents for the simultaneous determination of vitamin C and some vitamins belonging to the B group (thiamine, riboflavine, nicotinic acid and nicotinamide) in multivitamin preparations and in artichokes (Cynara cardunculus subsp. scolymus [L.] Hegi) were developed. Different experimental conditions were used, in terms of heat treatment, composition and pH of the extraction mixture, with particular attention to high-temperature steps; purification of the extracts with soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A MEKC method for the simultaneous analysis of some vitamins belonging to the B group (thiamine, riboflavine, nicotinic acid, and nicotinamide) and vitamin C in multivitamin preparations and in artichokes ( Cynara cardunculus subsp. scolymus (L.) Hegi ) has been developed . The total analysis time was less than 20 min.…”
Section: Vitaminsmentioning
confidence: 99%
“…A MEKC method for the simultaneous analysis of some vitamins belonging to the B group (thiamine, riboflavine, nicotinic acid, and nicotinamide) and vitamin C in multivitamin preparations and in artichokes ( Cynara cardunculus subsp. scolymus (L.) Hegi ) has been developed . The total analysis time was less than 20 min.…”
Section: Vitaminsmentioning
confidence: 99%
“…We found the migration distance of this compound to be shorter in comparison with that of niacin. Such behaviour is known from the literature 21 , 45 .…”
Section: Resultsmentioning
confidence: 78%
“…The identification of vitamin C and some vitamins belonging to the B group (thiamine, riboflavine, nicotinamide and nicotinic acid) in artichoke extracts was already reported [57]. It has been demonstrated that the nicotinic acid can inhibit lipolysis, acutely reducing plasma free fatty acid concentrations, and my act in much the same manner as cynarin [58].…”
Section: Resultsmentioning
confidence: 90%